The Potential Coordination of the Heat-Shock Proteins and Antioxidant Enzyme Genes of Aphidius gifuensis in Response to Thermal Stress - Kang, Zhi-Wei; Liu, Fang-Hua; Liu, Xiang; Yu, Wen-Bo; Tan, Xiao-Ling; Zhang, Shi-Ze; Tian, Hong-Gang; Liu, Tong-Xian (Frontiers in Physiology, 2017)
Abstract Aphidius gifuensis is one of the most important aphid natural enemies and has been successfully used to control Myzys persicae and other aphid species. High temperature in summer is one of the key barriers for the application of A. gifuensis in the field and greenhouse. In this work, we investigated the biological performance of A. gifuensis and the response of heat-shock proteins and antioxidant enzymes under high temperature. The results showed that A. gifuensis could not survive at 40oC and female exhibited a higher survival in 35oC. Furthermore, the short term exposure to high temperature negatively affected the performance of A. gifuensis especially parasitism efficiency. Under short-term heating, the expression of AgifsHSP, Agifl(2)efl, AgifHSP70, AgifHSP70-4 and AgifHSP90 showed an increased trend, whereas AgifHSP10 initially increased and then decreased. In 35oC, the expressions of Agifl(2)efl, AgifHSP70-4 and AgifHSP90 in female were higher than those in male, whereas the expression of AgifHSP70 exhibited an opposite trend. Besides the HSPs, we also quantified the expression levels of 11 antioxidant enzyme genes: AgifPOD, AgifSOD1, AgifSOD2, AgifSOD3, AgifCAT1, AgifCAT2, AgifGST1, AgifGST2, AgifGST3, AgifGST4 and AgifGST5. We found that the sex-specific expression of AgifSOD2, AgifSOD3, AgifPOD, AgifGST1 and AgifGST3 were highly consistent with sex-specific heat shock survival rates at 35oC. Furthermore, when the temperature was above 30 oC, the activities of GST, SOD, CAT and POD were significantly increased; however, there was no significant difference of the CAT activity between the male and female at 35 oC. Collectively, all of these results suggested that the protection of thermal damage is coordinated by HSPs and antioxidant enzymes in A. gifuensis. Based on the heat tolerance abilities of many aphid natural enemies, we also discussed an integrated application strategy of many aphid enemies in summer.